2021
DOI: 10.1136/jitc-2020-002292
|View full text |Cite
|
Sign up to set email alerts
|

Rapid corticosteroid taper versus standard of care for immune checkpoint inhibitor induced nephritis: a single-center retrospective cohort study

Abstract: BackgroundCurrent guidelines for treatment of immune checkpoint inhibitor (ICI)-induced nephritis are not evidence based and may lead to excess corticosteroid exposure. We aimed to compare a rapid corticosteroid taper to standard of care.MethodsRetrospective cohort study in patients with ICI-induced nephritis comparing a rapid taper beginning with 60 mg/day prednisone and tapered to 10 mg within 3 weeks to a historical control group that began 60 mg/day tapered to 10 mg within 6 weeks (standard of care). Renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…Lee et al examined outcomes among 13 patients with ICPi-AKI treated with a short duration of CS (tapered to ≤10 mg daily of prednisone equivalents within 3 weeks) versus 14 patients treated with a longer duration of CS, and found no significant difference in the time to renal recovery between groups. 8 Our data are consistent with these findings and expand on them in a larger and more generalizable cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Lee et al examined outcomes among 13 patients with ICPi-AKI treated with a short duration of CS (tapered to ≤10 mg daily of prednisone equivalents within 3 weeks) versus 14 patients treated with a longer duration of CS, and found no significant difference in the time to renal recovery between groups. 8 Our data are consistent with these findings and expand on them in a larger and more generalizable cohort.…”
Section: Discussionsupporting
confidence: 90%
“…Most studies have shown a relatively low risk of recurrence of ICI-associated AKI 16∼23% with ICI-rechallenge. Although this risk is low, it is important to note that patients are also at risk of developing another severe irAE in a different organ system [26 ▪ ]. Ultimately, the decision to rechallenge a patient with ICI is determined by their oncologist and is driven by the tumour's sensitivity to ICI, the patient's current response to therapy, the duration of ICI treatment prior to the ICI-induced AKI, the presence or absence of good alternative second-line therapies and patient preference.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective study suggested that the responses of ICI-induced nephritis were similar with rapid and standard corticosteroid tapering, an approach that can limit the secondary adverse events associated with long-term steroid regimens. Lee et al [ 22 ] showed that patients with ICI-induced nephritis have excellent kidney outcomes when given corticosteroids tapered rapidly over 3 weeks. In our survey, about half of the experts favored tapering over 4–6 weeks, whereas 25% selected a longer period of 12 weeks.…”
Section: Discussionmentioning
confidence: 99%